2004
DOI: 10.1016/j.jcv.2004.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, sequencing, expression, and purification of SARS-associated coronavirus nucleocapsid protein for serodiagnosis of SARS

Abstract: A novel coronavirus has been associated with a worldwide outbreak of atypical pneumonia referred to as Severe Acute Respiratory Syndrome (SARS-CoV). SARS-CoV nucleocapsid (N) protein has been cloned sequenced and expressed in Escherichia coli strain. Purified N protein was used to measure the SARS-CoV specific IgG antibodies from 16 SARS-CoV infected patients' sera and from 131 control subjects using ELISA assay. Specific antibody responses to the purified recombinant N protein after 10, 20, and 30 days of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 14 publications
1
58
0
Order By: Relevance
“…In an interesting study, the N gene of the CoV was found to be more effective for evaluating the codon usage bias than the S gene (Ahn et al, 2009). Studies reported that the N protein produced from prokaryotes has been used to generate specific antibodies against various animal coronaviruses including SARS (Loa et al, 2004;Timani et al, 2004;Wu et al, 2004aWu et al, , 2004bBlanchard et al, 2011). The recombinant antigenic N protein from hCoV OC43 used against the rabbit polyclonal antibodies specific for hCoV OC43 and did not crossreact with other coronaviruses (SARS CoV and hCoV 229E) (Liang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In an interesting study, the N gene of the CoV was found to be more effective for evaluating the codon usage bias than the S gene (Ahn et al, 2009). Studies reported that the N protein produced from prokaryotes has been used to generate specific antibodies against various animal coronaviruses including SARS (Loa et al, 2004;Timani et al, 2004;Wu et al, 2004aWu et al, , 2004bBlanchard et al, 2011). The recombinant antigenic N protein from hCoV OC43 used against the rabbit polyclonal antibodies specific for hCoV OC43 and did not crossreact with other coronaviruses (SARS CoV and hCoV 229E) (Liang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Since the specific antibodies to nucleocapsid (N) protein are most abundant in the sera from SARS patients (5), several groups have developed some recombinant N protein-based ELISAs. In general, these new assays are more specific and sensitive than the ELISA based on whole-virus lysate, but some false-positive results still occurred with sera from non-SARS patients or healthy people, even with sera collected several years before the SARS outbreak (3,7,8,(10)(11)(12).Since the N proteins of the known coronaviruses are relatively conserved, the expressed N protein of the SARS-CoV in Escherichia coli cross-reacts with polyclonal antisera of some known animal coronaviruses in antigenic group I, including transmissible gastroenteritis virus, feline infectious peritonitis virus, and canine coronavirus (9), which raised concerns of potential false positives when the recombinant N protein of the SARS-CoV, whole-virus antigen extracts, or virus-infected cells are used as reagents. However, this concern is very minimal, since the two known human coronaviruses (strains 229E and OC43) do not cause severe clinical diseases and we still do not have data about the prevalence of the antibodies to other coronaviruses or relevant microorganisms in human populations (4,6,8).…”
mentioning
confidence: 99%
“…Since the specific antibodies to nucleocapsid (N) protein are most abundant in the sera from SARS patients (5), several groups have developed some recombinant N protein-based ELISAs. In general, these new assays are more specific and sensitive than the ELISA based on whole-virus lysate, but some false-positive results still occurred with sera from non-SARS patients or healthy people, even with sera collected several years before the SARS outbreak (3,7,8,(10)(11)(12).…”
mentioning
confidence: 99%
“…Prokaryotic-expressed NPs have been used successfully as antigens in ELISA-based assays for the detection of antibodies specific to many viruses, including SARS-CoV and several animal coronaviruses (Blanchard et al, 2011;Loa et al, 2004;Timani et al, 2004;Wu et al, 2004). In the current study, large quantities of soluble recombinant HCoV-OC43 NP from E. coli were expressed and purified in the presence of 0.1% CHAPS.…”
Section: Discussionmentioning
confidence: 99%